Arrangement Model of Street Foot Vendors Culinary to Realize the Function of Spatial in Bengkayang Regency - Veneranda Rini Hapsari; Benedhikta Kikky Vuspitasari; Deffrinica Deffrinica (AIBPM Publisher, 2019)
This research aims to know the model of the arrangement for street vendors in culinary field with the aim to realize spatial function in Bengkayang district. So, it can increase the compatibility of doing activities among street vendors, so it is more directed and orderly. The research method used is a qualitative descriptive method. The research site is located in Bengakayang Regency. The research object is the street vendors. The information obtained comes from through the results of observations, interviews and documentation. The results of this study are the effectiveness of structuring and fostering street vendors in Bengkayang Regency, Bengkayang Subdistrict highly dependent on four main elements namely, location of trading, trading time, trading physical facilities and types of merchandise, and patterns of distribution of street vendors and street vendors service patterns. This will make it easier for local governments to organize and regulate street vendors who are scattered in Bengkayang regency.